Inhibition of epidermal growth factor receptor restores decidualization markers in stromal fibroblasts from women with endometriosis. Issue 4 (October 2014) - Erikson, David W.; Chen, Joseph C.; Piltonen, Terhi T.; Conti, Marco; Irwin, Juan C.; Giudice, Linda C.
Purpose: Decidualization comprises specific biochemical and morphological changes in uterine endometrium essential for establishment of pregnancy. This process is abnormal in women with endometriosis, a disorder in which endometrial-like tissue is present outside the uterus. The aim of this study was to restore cAMP-induced decidualization marker expression in endometrial stromal fibroblasts from women with endometriosis by using chemical inhibitors to PI3K/AKT/mammalian target of rapamycin (mTOR), mitogen-activated protein kinase (MAPK) and epidermal growth factor receptor (EGFR) signaling pathways in vitro. Methods: Endometrial stromal fibroblasts (eSF) from women with (eSFendo ) and without (eSFnon-endo ) endometriosis were treated with inhibitors to EGFR tyrosine kinase (gefitinib), mTOR (rapamycin) and MAPK kinase 1/2 (MEK1/2) (UO126) during 8-bromoadenosine 3′, 5′-cyclic monophosphate (8-br-cAMP)–stimulated decidualization. Decidualization was assessed by evaluating expression of insulin growth factor binding protein 1 (IGFBP1), prolactin (PRL) and forkhead box protein O1A (FOXO1A) by quantitative real-time PCR. Results: Gefitinib restored expression of decidualization markers in eSFendo to levels consistent with those in eSFnon-endo . Elevated levels of phosphorylated mTOR in eSFendo were reduced to levels found in eSFnon-endo, by gefitinib during treatment with 8-br-cAMP. Additional gene expression analyses suggested dysregulation of EGFR negative feedback regulators in eSFendo . Conclusions: Results implicate EGFR signaling as an underlying cause for aberrant cAMP-induced decidualization in women with endometriosis, and provide a potential target for management of infertility associated with the disease. The reduction of p-mTOR levels in eSFendo during 8-br-cAMP treatment suggests cooperation between EGR and protein kinase A signaling in the regulation of mTOR in eSF.